Desvendando o fã de Super-Heróis: performances, práticas de consumo e identidades - Becko, Larissa Tamborindenguy (Universidade do Vale do Rio dos Sinos, 2019)
The purpose of this work is to examine how Marvel and DC Comics superhero fans build their performances based on their consumption practices and how these contribute as identity elements for the individuals. The research, which presents a quantitative approach and a qualitative approach with ethnographic bias, seeks to analyze the fan culture, mainly based on the contributions of Jenkins (1992, 2006, 2009) and Hills (2002, 2015), the constructions of identity, taking into account the reflections of Hall (2003, 2006), García Canclini (1995, 2011), Martín-Barbero (1997, 2014), and Ortiz (2003), and consumption processes, essentially from Miller (2007, 2013) and Barbosa's & Campbell (2006) precepts, to reflect the multi-media character and the mainstream status that these characters have acquired. Empirical analyzes are made using the performance concept, by Schechner (2013) and Goffman (2009), as the methodological lens and indicate that the consumption of goods and media texts related to superheroes is fundamental so that the fans can create their identity narratives and position themselves within and for the fandom.
Keywords: Super-heróis; Cultura de fã; Consumo; Identidade; Performance; Superheroes; Fan culture; Consumption; Identity; Performance; Performance; ACCNPQ::Ciências Sociais Aplicadas::Comunicação